Titanium dioxide modified potassium feldspar heat-insulation composite pigment and filler as well as preparation method and application thereof
By modifying potash feldspar powder, combining titanium dioxide and lanthanum ceria, and using a liquid phase method to synthesize titanium dioxide modified potassium feldspar thermal insulation composite pigments and fillers, the existing coatings have single functions, poor radiation cooling capabilities and high costs. problem, achieving efficient thermal insulation, weather resistance and cost-effective coating performance.
Patent Information
- Application Number
- CN202411372027.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The existing reflective heat insulation coatings have single functions, poor radiation cooling capacity, inconsistent coating thickness and life, insufficient self-cleaning and weather resistance, and high coating costs due to the addition of expensive fillers such as titanium dioxide and zinc oxide powder.
By modifying potassium feldspar powder, combining titanium dioxide and lanthanum cerate, a titanium dioxide-modified potash feldspar thermal insulation composite pigment and filler is synthesized using a liquid phase method, taking advantage of the thermal insulation properties of lanthanum cerate and the hiding power of titanium dioxide, A composite material with a high specific heat capacity is formed, and the stability of the material is enhanced by silica coating.
It improves the heat resistance, weather resistance and heat insulation function of the coating, extends the service life of the coating, reduces the dosage of titanium dioxide, thereby reducing the cost of the coating and solving the problem of the coating fading easily.
Smart Images

Figure CN119331457A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating fillers, and specifically relates to a titanium dioxide modified potassium feldspar thermal insulation composite pigment filler and a preparation method and application thereof. Background Art
[0002] Titanium dioxide is a white filler with good hiding power and tinting power, and is widely used in architectural coatings. Due to economic development, social progress and the improvement of people's living standards, the construction industry and related coatings industries have developed, which has led to an increasing demand for titanium dioxide. On the other hand, the processing technology of titanium dioxide is complicated and environmental protection requirements are increasingly stringent, so the production cost of titanium dioxide has increased and the price has risen sharply. Potassium feldspar is an aluminum silicate mineral with a low price. It is mainly used in the glass and ceramic industries. Guangxi has rich potassium feldspar mineral resources, but its application range is limited.
[0003] Potassium feldspar is a potassium aluminosilicate mineral with a framework crystal structure composed of silicon and oxygen tetrahedrons. Its chemical formula is: K 2 O.Al 2 O 3 6SiO 2 ;Main ingredients: SiO 2 、Al 2 O 3 , K 2 O, CaO, etc. Potassium feldspar is often added to materials to improve its heat resistance, acid and alkali resistance, and strength due to its low thermal conductivity, stable chemical properties, and high hardness. In the invention patent with publication number CN115093754A "A multifunctional composite reflective cooling paint and its preparation method", 3-5 parts of potassium feldspar are added to make a multifunctional composite reflective cooling paint. The paint has good radiation cooling effect and has multiple functions such as waterproof, mildew-resistant, acid and alkali-resistant, and air purification. At the same time, the thickness, self-cleaning, weather resistance, and service life of the coating are improved, solving the problems of the existing reflective thermal insulation coatings with single function, poor radiation cooling ability, thick coating, inconsistent coating life, poor self-cleaning and weather resistance. However, the invention also adds 6-12 parts of composite titanium dioxide and 6-8 parts of zinc oxide powder. These relatively expensive fillers increase the cost of the coating.
[0004] Therefore, it is very necessary to research and develop a potassium feldspar modification method that is environmentally friendly, simple to prepare, and low in cost. Summary of the invention
[0005] The present invention aims to solve the above technical problems and provide a titanium dioxide modified potassium feldspar thermal insulation composite pigment filler to solve the problem of poor weather resistance and easy fading of exterior wall coatings, while enhancing the hardness and thermal insulation function of the coating. The prepared composite material can also reduce the amount of titanium dioxide used and reduce the cost of coatings.
[0006] The technical solution of the present invention is:
[0007] A titanium dioxide modified potassium feldspar heat-insulating composite pigment and filler comprises the following raw materials by weight: 40-55 parts of titanium dioxide, 30-45 parts of potassium feldspar, 10-15 parts of lanthanum cerate, 1.5-2.6 parts of coupling agent, 8-12 parts of sodium silicate and 0.5-1 part of sodium polycarboxylate.
[0008] Preferably, the particle size of the titanium dioxide of the present invention is 1200-1500 mesh, the particle size of the potassium feldspar is 500-800 mesh, and the particle size of the lanthanum cerate is 1800-2000 mesh.
[0009] The present invention uses abundant potassium feldspar powder as a core-coating matrix, titanium dioxide and lanthanum ceria as coating materials, and uses a liquid phase method to synthesize a thermal insulation composite pigment filler; when the raw materials are only stirred by adding water in a reactor, the powder is difficult to disperse evenly, and after adding sodium polycarboxylate, electrostatic repulsion and steric repulsion can be transmitted respectively, thereby enhancing the dispersion ability of the powder; the present invention uses KH550 as a powder surface modifier to make the powder particles urchin-shaped, which is conducive to the hydrophobic polymerization of the powder. In addition, the present invention uses lanthanum ceria as a thermal insulation material, which has strong reflection of near-infrared rays with high heat, and is synergistically coated with titanium dioxide, which is conducive to improving the thermal insulation performance of the composite material. The present invention uses sodium silicate as a silicon source, and adds it after adjusting the pH with sodium hydroxide solution to form a silicon dioxide coating on the surface of the composite material, which is conducive to improving the stability of the composite material.
[0010] The invention uses sodium silicate as a silicon source, has abundant raw material sources, low price, simple production process, and the coated titanium dioxide modified potassium feldspar has stronger stability.
[0011] Preferably, the method for preparing the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler of the present invention comprises the following steps:
[0012] S1. Weigh the raw material components according to their weight:
[0013] S2. The sodium polycarboxylate is divided into three parts according to a mass ratio of 8:3:7, namely, part A, part B, and part C; the mass ratio of the coupled chain is divided into three parts according to a mass ratio of 8:3:7, namely, part a, part b, and part c;
[0014] S3. First, titanium dioxide was dispersed in pure water, and then part A of sodium polycarboxylate was added, and after stirring, part a of a coupling chain was added, and the reaction was stirred to obtain a titanium dioxide slurry; lanthanum ceria was dispersed in pure water, and then part B of sodium polycarboxylate was added, and after stirring, part b of a coupling chain was added, and the reaction was stirred to obtain a lanthanum ceria slurry; potassium feldspar was dispersed in pure water, and then part C of sodium polycarboxylate was added, and after stirring, part c of a coupling chain was added, and the reaction was stirred to obtain a potassium feldspar slurry;
[0015] S4. The titanium dioxide slurry and lanthanum cerate slurry obtained in S3 are sequentially added to the potassium feldspar slurry and stirred for reaction;
[0016] S5. After adjusting the pH value to 10-12 with a 10% NaOH solution, slowly add sodium silicate and stir the reaction;
[0017] S6. The obtained slurry is filtered, dried and dispersed to obtain the titanium dioxide modified potassium feldspar thermal insulation composite pigment filler.
[0018] In the method of the present invention, potassium feldspar is used as the core, titanium dioxide is used for surface modification, lanthanum cerate is filled, and the outermost layer is stably coated with silicon dioxide to form a core-shell structure, so the order of adding materials cannot be changed.
[0019] Preferably, in step S2 of the present invention, the sodium polycarboxylate is divided into part A, part B and part C in a mass ratio of 8:3:7.
[0020] Preferably, in step S2 of the present invention, the even chain is divided into part a, part b and part c at a mass ratio of 8:3:7.
[0021] Too high or too low slurry concentration will affect the coating efficiency of the product. In order to obtain excellent coating efficiency, preferably, in step S3 of the present invention, the weight ratio of titanium dioxide to pure water is 1:1; the weight ratio of lanthanum cerate to pure water is 1:1; and the weight ratio of potassium feldspar to pure water is 1:1.
[0022] Preferably, in steps S3 and S4 of the present invention, the stirring reaction time is 25-35 min; in S5, the stirring reaction time is 35-45 min.
[0023] In order to avoid introducing other ions and affecting the purity of the product, preferably, in step S5 of the present invention, a NaOH solution with a mass fraction of 10% is used to adjust the pH.
[0024] The present invention also provides the use of the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler in exterior wall coatings. Specifically, the addition amount of the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler is 6-10% of the total mass of the exterior wall coating.
[0025] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0026] 1. The potassium feldspar in the titanium dioxide modified potassium feldspar thermal insulation composite pigment filler of the present invention has a higher specific heat capacity after modification. When applied to exterior wall paint, the temperature will not rise too high, which can effectively reduce the decomposition of pigment molecules and emulsion matrix, improve the heat resistance and weather resistance of the paint, so that the exterior wall paint has better thermal insulation function and is not easy to fade, which well solves the problem of poor weather resistance and easy fading of exterior wall paint in the prior art.
[0027] 2. The present invention uses titanium dioxide to modify potassium feldspar, and the prepared titanium dioxide modified potassium feldspar insulation composite pigment filler can replace part of titanium dioxide in exterior wall paint, thereby reducing the amount of titanium dioxide used and reducing the cost of exterior wall paint.
[0028] 3. The present invention uses titanium dioxide and lanthanum cerate to modify potassium feldspar, making the flat structure of potassium feldspar rough, increasing its specific surface area, which is beneficial to improving the compatibility of titanium dioxide modified potassium feldspar insulation composite pigment and filler with exterior wall resin emulsion. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is an electron microscope scanning image of the titanium dioxide modified potassium feldspar thermal insulation composite pigment filler in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] A titanium dioxide modified potassium feldspar heat-insulating composite pigment and filler is composed of the following parts by weight: 45 parts of titanium dioxide (particle size is 1250 mesh), 35 parts of potassium feldspar (particle size is 800 mesh), 13 parts of lanthanum cerate (particle size is 2000 mesh), 1.98 parts of KH-550, 10 parts of sodium silicate, and 0.72 parts of sodium polycarboxylate.
[0033] The preparation method of the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler comprises the following steps:
[0034] S1. Weigh the raw material components according to the above weight parts:
[0035] S2. The mass number of sodium polycarboxylate is divided into three parts, namely 0.32 parts, 0.12 parts, and 0.28 parts; the mass number of KH-550 is divided into 3 parts, namely 0.88 parts, 0.33 parts, and 0.77 parts;
[0036] S3. First, titanium dioxide was dispersed in pure water at a mass ratio of 1:1, and then 0.32 parts of sodium polycarboxylate were added, and 0.88 parts of KH-550 were added after stirring, and the reaction was stirred for 30 minutes to obtain a titanium dioxide slurry; lanthanum ceria was dispersed in pure water at a mass ratio of 1:1, and then 0.12 parts of sodium polycarboxylate were added, and 0.33 parts of KH-550 were added after stirring, and the reaction was stirred for 30 minutes to obtain a lanthanum ceria slurry; potassium feldspar was dispersed in pure water at a mass ratio of 1:1, and then 0.28 parts of sodium polycarboxylate were added, and 0.77 parts of KH-550 were added after stirring, and the reaction was stirred for 30 minutes to obtain a potassium feldspar slurry;
[0037] S4. The titanium dioxide slurry and lanthanum cerate slurry obtained in S3 are sequentially added to the potassium feldspar slurry and stirred for 30 min;
[0038] S5. After adding 10% NaOH solution by mass to adjust the pH value to 10, slowly add sodium silicate and stir the reaction for 40 minutes;
[0039] S6. The obtained slurry is filtered, dried, and dispersed to obtain a titanium dioxide-modified potassium feldspar thermal insulation composite pigment filler, as shown in the electron microscope image. Figure 1 .
[0040] Example 2
[0041] A titanium dioxide modified potassium feldspar heat-insulating composite pigment and filler is composed of the following parts by weight: 40 parts of titanium dioxide (particle size is 1500 mesh), 30 parts of potassium feldspar (particle size is 800 mesh), 10 parts of lanthanum cerate (particle size is 2000 mesh), 1.62 parts of KH-550, 8 parts of sodium silicate, and 0.54 parts of sodium polycarboxylate.
[0042] The preparation method of the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler comprises the following steps:
[0043] S1. Weigh the raw material components according to the above weight parts:
[0044] S2. The mass number of sodium polycarboxylate is divided into three parts, 0.24 parts, 0.09 parts, and 0.21 parts respectively; the mass number of KH-550 is divided into 3 parts, 0.72 parts, 0.27 parts, and 0.63 parts respectively;
[0045] S3. First, titanium dioxide was dispersed in pure water at a mass ratio of 1:1, and then 0.24 parts of sodium polycarboxylate were added, and 0.72 parts of KH-550 were added after stirring, and the reaction was stirred for 30 minutes to obtain a titanium dioxide slurry; lanthanum ceria was dispersed in pure water at a mass ratio of 1:1, and then 0.09 parts of sodium polycarboxylate were added, and 0.27 parts of KH-550 were added after stirring, and the reaction was stirred for 30 minutes to obtain a lanthanum ceria slurry; potassium feldspar was dispersed in pure water at a mass ratio of 1:1, and then 0.21 parts of sodium polycarboxylate were added, and 0.63 parts of KH-550 were added after stirring, and the reaction was stirred for 30 minutes to obtain a potassium feldspar slurry;
[0046] S4. The titanium dioxide slurry and lanthanum cerate slurry obtained in S3 are sequentially added to the potassium feldspar slurry and stirred for 30 min;
[0047] S5. After adding 10% NaOH solution by mass to adjust the pH value to 10, slowly add sodium silicate and stir the reaction for 40 minutes;
[0048] S6. The obtained slurry is filtered, dried and dispersed to obtain the titanium dioxide modified potassium feldspar thermal insulation composite pigment filler.
[0049] Example 3
[0050] A titanium dioxide modified potassium feldspar heat-insulating composite pigment and filler is composed of the following parts by weight: 55 parts of titanium dioxide (particle size is 1200 mesh), 45 parts of potassium feldspar (particle size is 500 mesh), 15 parts of lanthanum cerate (particle size is 1800 mesh), 2.52 parts of KH-550, 12 parts of sodium silicate, and 1.08 parts of sodium polycarboxylate.
[0051] The preparation method of the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler comprises the following steps:
[0052] S1. Weigh the raw material components according to the above weight parts:
[0053] S2. The mass number of sodium polycarboxylate is divided into three parts, namely 0.48 parts, 0.18 parts, and 0.42 parts; the mass number of KH-550 is divided into 3 parts, namely 1.12 parts, 0.42 parts, and 0.98 parts;
[0054] S3. First, titanium dioxide was dispersed in pure water at a mass ratio of 1:1, and then 0.48 parts of sodium polycarboxylate were added, 1.12 parts of KH-550 were added after stirring, and the reaction was stirred for 30 minutes to obtain a titanium dioxide slurry; lanthanum ceria was dispersed in pure water at a mass ratio of 1:1, and then 0.18 parts of sodium polycarboxylate were added, and 0.42 parts of KH-550 were added after stirring, and the reaction was stirred for 30 minutes to obtain a lanthanum ceria slurry; potassium feldspar was dispersed in pure water at a mass ratio of 1:1, and then 0.42 parts of sodium polycarboxylate were added, and 0.98 parts of KH-550 were added after stirring, and the reaction was stirred for 30 minutes to obtain a potassium feldspar slurry;
[0055] S4. The titanium dioxide slurry and lanthanum cerate slurry obtained in S3 are sequentially added to the potassium feldspar slurry and stirred for 30 min;
[0056] S5. After adding 10% NaOH solution to adjust the pH to 12, slowly add sodium silicate and stir the reaction for 40 minutes;
[0057] S6. The obtained slurry is filtered, dried and dispersed to obtain the titanium dioxide modified potassium feldspar thermal insulation composite pigment filler.
[0058] In order to verify the superiority of the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler formula of the present invention, the following comparative examples are set up, as follows:
[0059] Comparative Example 1: The difference from Example 1 is that titanium dioxide is replaced with potassium feldspar, and the rest is the same as Example 1.
[0060] Comparative Example 2: The difference from Example 1 is that potassium feldspar is replaced with titanium dioxide, and the rest is the same as Example 1.
[0061] Comparative Example 3: The difference from Example 1 is that lanthanum ceria is removed, and the sodium polycarboxylate and KH-550 that match lanthanum ceria are also removed, and the rest is the same as Example 1.
[0062] Comparative Example 4: The difference from Example 1 is that KH-550 is removed, and the parts related to KH-550 in the method are removed, and the rest are the same as Example 1.
[0063] Comparative Example 5: The difference from Example 1 is that sodium silicate is removed, and the parts related to sodium silicate in the method are removed, and the rest are the same as Example 1.
[0064] The performance tests were performed on the above-mentioned Example 1 and Comparative Examples 1-5, and the results are shown in Table 1.
[0065] Table 1 Performance of different titanium dioxide modified potassium feldspar thermal insulation composite pigments and fillers
[0066]
[0067] It can be seen from Table 1 that the performance of the titanium dioxide modified potassium feldspar insulation composite pigment filler is equivalent to that of pure titanium dioxide, and can replace titanium dioxide for use in exterior wall coatings; the composite material of Comparative Example 1 mainly contains potassium feldspar, and has low whiteness and hiding power, a small specific surface area of the material, and therefore a small oil absorption; the composite material in Comparative Example 2 mainly contains titanium dioxide, and has high whiteness and hiding power. Because of its small particle size, it has a smaller specific surface area and a lower oil absorption; in Comparative Example 3, lanthanum ceria is removed from the composite material, and the whiteness and hiding power are slightly reduced, and the particle size of the composite material is smaller than that of Example 1, so the oil absorption is slightly reduced; in Comparative Example 4, the surfactant KH-550 is removed, the material composite efficiency is low, the whiteness and hiding power are low, and the oil absorption is average; in Comparative Example 5, the outermost layer of the silica coating is removed, the material surface is rough, the oil absorption is increased, but the whiteness and contrast ratio do not change much. In summary, it can be seen that the titanium dioxide modified potassium feldspar thermal insulation composite pigment filler obtained by adopting the formula of the present invention has good comprehensive performances of whiteness, hiding power and oil absorption.
[0068] In order to verify the superiority of the method for preparing the thermal insulation composite pigment and filler of titanium dioxide modified potassium feldspar of the present invention, the following comparative examples are set up, as follows:
[0069] Comparative Example 6: The difference from Example 2 is that the preparation method of the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler is:
[0070] S3. Disperse titanium dioxide and potassium feldspar in pure water (the amount of water added is the sum of the corresponding amounts of water added of titanium dioxide and potassium feldspar in Example 2), then add sodium polycarboxylate (the amount added is the sum of the corresponding amounts added of titanium dioxide and potassium feldspar in Example 2), stir evenly, add KH-550 (the amount added is the sum of the corresponding amounts added of titanium dioxide and potassium feldspar in Example 2), stir and react for 30 minutes to obtain a titanium dioxide composite potassium feldspar slurry; disperse lanthanum ceria in pure water at a mass ratio of 1:1, then add 0.0.6 parts of sodium polycarboxylate, stir evenly, add 0.19 parts of KH-550, stir and react for 30 minutes to obtain a lanthanum ceria slurry;
[0071] S4. The lanthanum cerate slurry obtained in S3 was added to the titanium dioxide composite potassium feldspar slurry and the reaction was stirred for 30 min;
[0072] The rest is the same as Example 2.
[0073] Comparative Example 7
[0074] The difference from Example 2 is that: after all the powders of titanium dioxide, potassium feldspar and lanthanum cerate are mixed, water is added (the amount of water added is the sum of the corresponding amounts of water added of titanium dioxide, potassium feldspar and lanthanum cerate in Example 2) to form a slurry, and then sodium polycarboxylate and KH-550 are added and stirred for reaction for 30 minutes; the rest is the same as Example 2.
[0075] Comparative Example 8
[0076] The difference from Example 2 is:
[0077] S1-S3 are the same as in Example 2;
[0078] S4. The pH value of each slurry was adjusted to 10 with a 10% NaOH solution;
[0079] S5. Sodium silicate was divided into three parts according to a mass ratio of 8:3:7, and the corresponding parts were mixed with the titanium dioxide slurry, lanthanum cerate slurry and potassium feldspar slurry after adjusting the pH value, stirred for 40 minutes, and then all the sodium silicate modified slurry was mixed and stirred for 30 minutes;
[0080] The rest is the same as Example 2. The performance of the titanium dioxide modified potassium feldspar thermal insulation composite pigments and fillers prepared in Example 2 and Comparative Examples 6-8 was tested, and the results are shown in Table 2.
[0081] Table 2 Performance test results of different titanium dioxide modified potassium feldspar thermal insulation composite pigments and fillers
[0082]
[0083] In Comparative Example 6, titanium dioxide and potassium feldspar are mixed and then a modifier is added. Although the surface of the powder is modified, the composite efficiency is not high. Therefore, the whiteness and hiding rate of the composite pigment filler prepared in Comparative Example 6 are low. Similarly, the whiteness and hiding rate of Comparative Example 7 are not high. In Comparative Example 8, the powder is first coated with silicon dioxide and then composited. The silicon dioxide covers the surface modifier, so the powder composite is unsuccessful. Therefore, its whiteness and hiding rate are very low, but the surface of the particles is coated with silicon dioxide, the specific surface area is small, and the oil absorption is low. In summary, the titanium dioxide modified potassium feldspar thermal insulation composite pigment filler prepared by the specific method of the present invention has good comprehensive performance in whiteness, hiding rate and oil absorption.
[0084] Example 4: Application of titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler in exterior wall coatings.
[0085] An exterior wall paint containing titanium dioxide modified potassium feldspar composite heat-insulating pigment and filler, comprising the following parts by weight:
[0086] 32 parts of water, 3 parts of cellulose, 0.2 parts of multifunctional additive, 0.6 parts of dispersant, 2 parts of ethylene glycol, 0.2 parts of wetting agent, 1.4 parts of film-forming aid, 0.4 parts of defoaming agent, 0.2 parts of bactericide, 8 parts of titanium dioxide modified potassium feldspar insulation composite pigment and filler prepared in Example 1, 5 parts of kaolin, 5 parts of wollastonite, 2 parts of barium sulfate, 23 parts of heavy calcium, and 20 parts of aqueous resin emulsion.
[0087] The cellulose is hydroxyethyl cellulose with a brand name of 250HBR; the multifunctional additive is 2-amino-2-methyl-1-propanol containing 5% by mass with a brand name of Amp-95; the wetting agent is octylphenol polyoxyethylene ether with a brand name of CX-407; the film-forming additive is alcohol ester twelve; the defoaming agent is a composite of organic polyether ester and mineral oil with a brand name of DF-18; the bactericide is a mixture of formaldehyde releaser and Kathon with a brand name of CHS5; and the emulsion is styrene acrylic emulsion with a brand name of 5939.
[0088] A method for preparing an exterior wall coating containing titanium dioxide modified potassium feldspar composite thermal insulation pigment and filler is as follows:
[0089] S1. Weigh the raw material components according to the above weight parts;
[0090] S2. First, add cellulose and multifunctional additives to water in turn for dispersion, adjust the speed to 800 rpm, and stir to dissolve for 10 min;
[0091] S4. Reduce the speed to 700 rpm, add dispersant, wetting agent and 1 / 2 defoamer in sequence, and stir and disperse for 10 minutes;
[0092] S5. The titanium dioxide-modified potassium feldspar thermal insulation composite pigment prepared in Example 1, kaolin, wollastonite, barium sulfate and heavy calcium were sequentially added, the speed was adjusted to 1500 rpm, and the dispersion was continued for 40 min.
[0093] S6. Adjust the speed to 700 rpm, slowly add ethylene glycol and film-forming aid, and stir and disperse for 5 minutes;
[0094] S7. Add the aqueous resin emulsion and the remaining defoamer, stir and disperse for 15 minutes, and filter with a 200-mesh sieve to obtain an exterior wall coating containing the titanium dioxide-modified potassium feldspar thermal insulation composite pigment and filler prepared in Example 1.
[0095] Comparative Example A
[0096] The only difference from Example A is that the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler prepared in Example 1 is replaced by the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler prepared in Comparative Example 1, and the rest is the same as Example 4.
[0097] Comparative Example B
[0098] The only difference from Example A is that the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler prepared in Example 1 is replaced by the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler prepared in Comparative Example 2, and the rest is the same as Example 4.
[0099] Comparative Example C
[0100] The only difference from Example A is that the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler prepared in Example 1 is replaced by the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler prepared in Comparative Example 3, and the rest is the same as Example 4.
[0101] Comparative Example D
[0102] The only difference from Example A is that the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler prepared in Example 1 is replaced by the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler prepared in Comparative Example 4, and the rest is the same as Example 4.
[0103] Comparative Example E
[0104] The only difference from Example A is that the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler prepared in Example 1 is replaced by the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler prepared in Comparative Example 5, and the rest is the same as Example 4.
[0105] The contrast ratio, thermal insulation temperature difference, color heat resistance and scrub resistance of the exterior wall coatings containing titanium dioxide modified potassium feldspar thermal insulation composite pigments and fillers prepared in the above Example 4 and Comparative Example AE were tested, and the results are shown in Table 3. Among them, the contrast ratio and scrub resistance were tested in accordance with the requirements of the national standard GB / T 9755-2014 "Synthetic resin emulsion exterior wall coatings"; the thermal insulation temperature difference was tested in accordance with the requirements of the industry standard JG / T 1040-2020 "Heat reflective insulation coatings for building exterior surfaces"; the color heat resistance was tested by adjusting the coating to carbon black, then placing it in a curing box and heating it at 50°C for 1000 hours, and then taking a sample plate to observe the color fading.
[0106] Table 3 Performance of different exterior wall coatings
[0107]
[0108] The following conclusions can be drawn from Table 3:
[0109] (1) The coating contrast ratio of the product in Example 4 is relatively high, close to the coating contrast ratio of pure titanium dioxide added in Comparative Example B; while in Comparative Example A, potassium feldspar not modified by titanium dioxide is added, and the coating contrast ratio is the worst; the coating contrast ratio of the titanium dioxide-modified potassium feldspar composite thermal insulation pigment added in Comparative Example C does not contain lanthanum cerate thermal insulation material, which does not change much, so it can be seen that lanthanum cerate has little effect on the coating contrast ratio; the thermal insulation composite pigment added in Comparative Example D is not modified by KH-550, and the raw material composite efficiency is not high, so the coating contrast ratio is poor; the thermal insulation composite pigment in Comparative Example E is not wrapped with silica, and its stability is poor. After adding the paint and stirring, the structure is destroyed, resulting in a decrease in the coating contrast ratio;
[0110] (2) Among the heat-insulating composite pigments and fillers prepared in several synthesis schemes, the composite heat-insulating pigment and filler added in Comparative Example C does not contain lanthanum cerate heat-insulating material, so the heat-insulating temperature difference of the coating is poor. The composite heat-insulating pigment and filler added in Comparative Example A does not contain titanium dioxide, and the temperature of the coating is poor. It can be seen that titanium dioxide also has a certain influence on the heat-insulating effect of the coating;
[0111] (3) The heat-insulating composite pigment added in Comparative Example B does not contain potassium feldspar, and the coating has poor heat resistance. The coating is easy to fade when heated, and the coating has poor washability. It can be seen that adding potassium feldspar to the coating is beneficial to improving the color heat resistance and washability of the coating.
[0112] In summary, the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler prepared by the synergistic effect of the formula and method of the present invention, when used in exterior wall coatings, can solve the problems of poor weather resistance and easy fading of exterior wall coatings, and at the same time can enhance the hardness and thermal insulation function of the coating. The prepared composite material can also reduce the amount of titanium dioxide used and reduce the cost of coatings.
[0113] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.
Claims
1. A titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler, characterized in that: The invention comprises the following raw materials by weight: 40-55 parts of titanium dioxide, 30-45 parts of potassium feldspar, 10-15 parts of lanthanum cerate, 1.5-2.6 parts of coupling agent, 8-12 parts of sodium silicate and 0.5-1 part of sodium polycarboxylate.
2. The titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler as claimed in claim 1, characterized in that: The particle size of the titanium dioxide is 1200-1500 mesh, the particle size of the potassium feldspar is 500-800 mesh, and the particle size of the lanthanum cerate is 1800-2000 mesh.
3. The method for preparing the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler as claimed in claim 1, characterized in that: The following steps are involved: S1. Weigh the raw material components according to their weight: S2. The sodium polycarboxylate is divided into three parts, namely, part A, part B, and part C; the coupling agent is divided into 3 parts, namely, part a, part b, and part c; S3. First, titanium dioxide was dispersed in pure water, and then part A of sodium polycarboxylate was added, and after stirring, part a of a coupling chain was added, and the reaction was stirred to obtain a titanium dioxide slurry; lanthanum ceria was dispersed in pure water, and then part B of sodium polycarboxylate was added, and after stirring, part b of a coupling chain was added, and the reaction was stirred to obtain a lanthanum ceria slurry; potassium feldspar was dispersed in pure water, and then part C of sodium polycarboxylate was added, and after stirring, part c of a coupling chain was added, and the reaction was stirred to obtain a potassium feldspar slurry; S4. The titanium dioxide slurry and lanthanum cerate slurry obtained in S3 are sequentially added to the potassium feldspar slurry and stirred for reaction; S5. After adjusting the pH value to 10-12, slowly add sodium silicate and stir the reaction; S6. The obtained slurry is filtered, dried and dispersed to obtain the titanium dioxide modified potassium feldspar thermal insulation composite pigment filler.
4. The method for preparing the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler as claimed in claim 3, characterized in that: In the step S2, the sodium polycarboxylate is divided into part A, part B and part C according to a mass ratio of 8:3:
7.
5. The method for preparing the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler as claimed in claim 3, characterized in that: In step S2, the even link is divided into a portion, b portion, and c portion according to a mass ratio of 8:3:
7.
6. The method for preparing the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler as claimed in claim 3, characterized in that: In the step S3, the weight ratio of titanium dioxide to pure water is 1:1; the weight ratio of lanthanum cerate to pure water is 1:1; and the weight ratio of potassium feldspar to pure water is 1:
1.
7. The method for preparing the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler as claimed in claim 3, characterized in that: In the steps S3 and S4, the stirring reaction time is 25-35 min; in the step S5, the stirring reaction time is 35-45 min.
8. The method for preparing the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler as claimed in claim 3, characterized in that: In the step S5, the pH is adjusted using a NaOH solution with a mass fraction of 10%.
9. Use of the titanium dioxide modified potassium feldspar thermal insulation composite pigment and filler as claimed in claim 1 or 2 in exterior wall coatings.
10. The use of the titanium dioxide modified potassium feldspar heat-insulating composite pigment and filler in exterior wall coatings as claimed in claim 9, characterized in that: The addition amount of the titanium dioxide modified potassium feldspar heat insulation composite pigment and filler is 6-10% of the total mass of the exterior wall paint.
Citation Information
Patent Citations
Multifunctional composite reflective cooling coating and preparation method thereof
CN115093754A
Silicon oxide coated titanium dioxide pigment and coating technology
CN102352135A
Nanocomposite wall paint and preparation method thereof
CN105062278A
Reflective heat-insulation lanthanum cerate color paste and preparation method thereof
CN113801521A
Thermosetting Epoxy powder coating composition fordual top coatingand its coating system
KR1020050068345A